Self-supporting film laminate for lithium secondary battery anode and method for manufacturing same

By using a self-contained film laminate containing a tri-stage copolymer and a fluorine-based resin, the problem of insufficient mechanical properties and adhesion of the anode of the lithium secondary battery is solved, and efficient manufacturing cost reduction is achieved.

CN119495701APending Publication Date: 2025-02-21HYUNDAI MOTOR CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311663633.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-14
Filing Date
2023-12-06
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The prior art is difficult to develop dry electrodes with excellent mechanical properties, moderate elongation, excellent adhesion between the independent film and the current collector, and high flexibility, resulting in a high manufacturing cost of lithium secondary batteries.

Method used

The self-reliable film laminate adopts a binder including a triblock copolymer, the first self-reliable film comprises a first anode active material, a first conductive material and a triblock copolymer binder, and the second self-reliable film comprises a second The anode active material, the second conductive material and the fluorine-based resin binder form a laminate by a stacking and calendering process.

Benefits of technology

The excellent mechanical properties, good adhesion and flexibility of the lithium secondary battery anode are achieved, and the manufacturing cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495701A_ABST
    Figure CN119495701A_ABST
Patent Text Reader

Abstract

The present invention provides a self-supporting film laminate for an anode of a lithium secondary battery and a method for manufacturing the same, the self-supporting film laminate comprising a first self-supporting film and a second self-supporting film, the first self-supporting film comprising a first anode active material, a first conductive material, and a first binder comprising a triblock copolymer, the second free-standing membrane comprises a second anode active material, a second conductive material, and a second binder comprising a fluorine-based resin, in which the triblock copolymer comprises a soft block derived from an aliphatic or alicyclic diene monomer and exhibiting a rubber phase at room temperature and a first hard block and a second hard block derived from an aliphatic or alicyclic diene monomer and exhibiting a rubber phase at room temperature; a first hard block and a second hard block are each attached to both ends of the soft block, derived from an aromatic ring-containing ethylenically unsaturated monomer and exhibiting a glass phase at room temperature, the first binder being in the form of a discontinuous column, and a second electrode connected between any one of the first anode active material domain or the first conductive material domain and the other of the first anode active material domain or the first conductive material domain.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the priority of Korean Patent Application No. 10-2023-0106488 filed in the Korean Intellectual Property Office on August 14, 2023, the contents of which are incorporated herein by reference. Technical Field

[0003] The present invention relates to a self-supporting film laminate for lithium secondary battery anodes, and a method for producing the same, wherein the self-supporting film laminate uses a binder containing a triblock copolymer containing a soft block and a hard block. Background Art

[0004] Since they were first commercialized in the 1990s, lithium secondary batteries have been widely used in the portable electronics market and continue to receive attention as the most studied energy storage system. Due to their characteristics such as high driving voltage, high energy density, low self-discharge rate, high-speed performance and long cycle stability, lithium secondary batteries meet the conditions required to be suitable as an energy source for electric vehicles.

[0005] However, there are still three major issues with lithium secondary batteries used in electric vehicles: safety, service time, and cost. The use of solid-state batteries can solve the safety and service time issues, but the cost issue has hindered the widespread application of lithium secondary batteries, so a lot of research is being conducted to reduce the cost of lithium secondary batteries.

[0006] Reducing the energy consumption required for manufacturing or increasing the thickness of the electrode is one of the most effective ways to reduce the manufacturing cost of lithium secondary batteries. In a typical method of manufacturing an electrode, a slurry obtained by mixing an electrode active material, a polymer binder and a conductive additive in water or an organic solvent is used to cast a collector, and the resulting product is dried and pressed to form an electrode, but in this way, the energy required to make the slurry and coat the collector accounts for about 50% of the energy consumed in the entire manufacturing process, so a solvent-free dry electrode manufacturing method has been studied to reduce the manufacturing cost of lithium secondary batteries.

[0007] Despite extensive research on dry electrode manufacturing methods, dry electrodes with excellent mechanical properties, not too high elongation to facilitate mass production, excellent adhesion of the self-standing film to the collector, and high flexibility have not yet been successfully developed, which requires further research and development. Summary of the invention

[0008] One aspect of the present invention provides a self-standing film laminate for a lithium secondary battery anode, the self-standing film laminate having excellent mechanical properties, satisfactory elongation, excellent adhesion to a current collector, and excellent flexibility, and a method for manufacturing the same.

[0009] In one aspect, a self-supporting film laminate suitable for a lithium secondary battery anode is provided, the self-supporting film laminate comprising (i) a first self-supporting film and (ii) a second self-supporting film, the first self-supporting film comprising a) a first anode active material, b) a first conductive material, and c) a first binder comprising a triblock copolymer; the second self-supporting film comprising a) a second anode active material, b) a second conductive material, and c) a second binder comprising a fluorine-based resin, wherein the triblock copolymer comprises a soft block and a first hard block and a second hard block, the soft block being derived from an aliphatic or alicyclic diene monomer and presenting a rubber phase at room temperature, the first hard block and the second hard block being each connected to both ends of the soft block, being derived from an aromatic ring-containing ethylenically unsaturated monomer and presenting a glass phase at room temperature, and the first binder being in a discontinuous columnar form, connected between any one of i) the first anode active material domain or ii) the first conductive material domain and the other of a) the first anode active material domain or b) the first conductive material domain.

[0010] On the other hand, a self-supporting film laminate for a lithium secondary battery anode is provided, wherein the self-supporting film laminate includes a first self-supporting film and a second self-supporting film, the first self-supporting film includes a first anode active material, a first conductive material and a first binder comprising a triblock copolymer, and the second self-supporting film includes a second anode active material, a second conductive material and a second binder comprising a fluorine-based resin. In this case, the triblock copolymer may include a soft block and a first hard block and a second hard block, the soft block is derived from an aliphatic or alicyclic diene monomer and presents a rubber phase at room temperature, the first hard block and the second hard block are each connected to the two ends of the soft block, derived from an aromatic ring-containing ethylenically unsaturated monomer and presents a glass phase at room temperature, and the first binder may be in a non-continuous columnar form, connected between any one of the first anode active material domain or the first conductive material domain and the first anode active material domain or the first conductive material domain.

[0011] According to another aspect of the present invention, there are provided an anode for a lithium secondary battery comprising a self-supporting film laminate for an anode of a lithium secondary battery, a lithium secondary battery comprising an anode for a lithium secondary battery, a method for manufacturing the self-supporting film laminate for an anode of a lithium secondary battery, and a method for manufacturing an anode for a lithium secondary battery.

[0012] In some aspects, in the self-standing film laminate as disclosed herein, suitably, the thickness ratio of the first self-standing film to the second self-standing film is from 1:0.01 to 1:0.49.

[0013] In some aspects, in the self-standing film laminate as disclosed herein, suitably, the film laminate comprises a three-layer structure in which a first self-standing film is stacked on each of an upper side and a lower side of a second self-standing film.

[0014] In some aspects, in the self-standing film laminate as disclosed herein, suitably, the film laminate comprises a repeated alternating stacking structure of a first self-standing film and a second self-standing film.

[0015] In some aspects, in the self-standing film laminate as disclosed herein, suitably, the first anode active material domains or the first conductive material domains are connected with the first binder in the form of non-continuous columns to form a three-dimensional network structure.

[0016] In some aspects, in the self-standing film laminate as disclosed herein, suitably, the first adhesive has an average width perpendicular to the machine direction of 0.1 μm to 2 μm.

[0017] In some aspects, in the self-standing film laminate as disclosed herein, suitably, the first and second glass transition temperatures corresponding to the first and second hard blocks, respectively, are independently 50°C to 120°C, and the third glass transition temperature corresponding to the soft block is -120°C to -50°C.

[0018] In some aspects, in the self-standing film laminate as disclosed herein, suitably, the soft block is derived from an aliphatic diene-based monomer comprising at least one selected from butadiene-based monomers, pentadiene-based monomers, and hexadiene-based monomers.

[0019] In some aspects, in the self-standing film laminate as disclosed herein, suitably, the first hard block and the second hard block are each independently derived from an aromatic ring-containing ethylenically unsaturated monomer comprising at least one of a styrene-based monomer and an aromatic (meth)acryloyl monomer.

[0020] In one aspect, a negative electrode of a lithium secondary battery is provided, comprising the composition as described herein.

[0021] In one aspect, a lithium secondary battery is provided, comprising the negative electrode as described herein.

[0022] In one aspect, there is provided a vehicle comprising a lithium secondary battery as described herein.

[0023] As used herein, the term "self-standing" refers to a sheet that is in a form that can be handled as an independent sheet without the aid of a substrate or carrier. Thus, the term "self-standing" can have the same meaning as "self-supporting".

[0024] The term "all-solid-state battery" as used herein includes or refers to a rechargeable battery (including a secondary battery) including a solid electrolyte (e.g., a gel or polymer (cured)), which may include ionomers and other electrolytic components for transporting ions between the electrodes of the battery. In one aspect, the lithium secondary battery mentioned herein is an all-solid-state battery.

[0025] As referred to herein, the rubber phase or rubbery state is above the Tg (glass transition temperature) of the material, i.e., where the material can be in a more rubbery state and relatively soft and pliable. Thus, when the material described herein forms a rubbery phase at room temperature (e.g., 25° C.), the material can be above its glass transition temperature and can be in a relatively rubbery or more pliable state at room temperature (25° C.).

[0026] As referred to herein, a glassy phase or glassy state is below the Tg (glass transition temperature) of a material, and wherein the material may be in a more rigid or glass-like configuration. Thus, when a material described herein forms a glassy phase at room temperature (e.g., 25° C.), at room temperature (25° C.) the material may be below its glass transition temperature and may be in a relatively rigid or hardened state.

[0027] The term "all-solid-state battery" used herein refers to a rechargeable secondary battery comprising a solid electrolyte (e.g., a gel or polymer (cured)), which may include ionomers and other electrolyte components for transferring ions between the electrodes of the battery. In a certain aspect, the lithium secondary battery mentioned herein is an all-solid-state battery.

[0028] The term "self-standing film or laminate or sheet" or other similar terms used herein include that the film or laminate or sheet can be in sheet form and can be handled as an independent sheet without the aid of a substrate or carrier. Therefore, the term "self-standing" can have the same meaning as "self-supporting".

[0029] The term "block polymer" as referred to herein includes polymers comprising two or more chemically distinct regions or segments (referred to as "blocks"), typically linked in a linear manner, such as a polymer comprising chemically distinct units that are linked (covalently bonded) end-to-end relative to the polymeric functional groups, rather than being linked (covalently bonded) in a pendant or grafted manner. In one aspect, the block polymer may comprise (i) a first polymer block comprising at least 5, 10, 20, or 30 first repeating units; and (ii) a second polymer block comprising at least 5, 10, 20, or 30 second repeating units.

[0030] As referred to herein, the terms "soft block" and "hard block" mean that the respective polymer units or parts are different in, for example, structure and one or more properties. In some aspects, the soft block may have a lower glass transition temperature or melting temperature (e.g., below room temperature) than the hard block, and the hard block may have a higher glass transition temperature or melting temperature (e.g., above room temperature) than the application temperature of the formed block copolymer material. In certain embodiments, the difference in Tg of the hard block and the soft block may, for example, reach or exceed, for example, 3°C, 5°C, 10°C, 20°C, or 30°C.

[0031] Other aspects are disclosed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The above and other aspects, features and other advantages of the present invention will be more clearly understood through the following detailed description in conjunction with the accompanying drawings, in which:

[0033] Figure 1A and Figure 1B is a SEM image of the first self-standing film according to Manufacturing Example 1-1;

[0034] Figure 1C is a diagram showing a network structure formed in the self-standing film according to Manufacturing Example 1-1;

[0035] Figure 2A is a SEM image of a composition (mixed powder) for forming a self-supporting film before manufacturing the first self-supporting film of Manufacturing Example 1-1;

[0036] Figure 2B Is manufacturing Figure 2A SEM image of SBS powder before mixing the powder as shown in;

[0037] Figure 3A is an image taken after evaluating the flexibility of the self-standing film laminate of Example 1 according to Experimental Example 3;

[0038] Figure 3B is an image taken after evaluating the flexibility of the self-standing film of Comparative Example 1 according to Experimental Example 3; and

[0039] Figure 3C This is an image taken after evaluating the flexibility of the self-standing film of Reference Example 1 according to Experimental Example 3. DETAILED DESCRIPTION

[0040] Exemplary embodiments of the present invention will now be described in detail with reference to the accompanying drawings.

[0041] Hereinafter, a self-standing film laminate for a lithium secondary battery anode and a method of manufacturing the same will be described in detail so that those skilled in the art to which the present invention pertains can easily practice the present invention.

[0042] Self-supporting film laminate for lithium secondary battery anode

[0043] The self-standing film laminate for a lithium secondary battery anode of the present invention is a laminate including a first self-standing film and a second self-standing film.

[0044] The first self-supporting film

[0045] The first self-standing film includes a first binder, a first anode active material, and a first conductive material.

[0046] The first binder may include a triblock copolymer. In this case, the triblock copolymer may include a soft block and a first hard block and a second hard block, the soft block is derived from an aliphatic or alicyclic diene monomer and presents a rubber phase at room temperature, the first hard block and the second hard block are each connected to the two ends of the soft block, derived from an aromatic ring-containing ethylenically unsaturated monomer and presents a glass phase at room temperature, and the first binder including the triblock copolymer may be in a non-continuous columnar form, connected between any one of the first anode active material domain or the first conductive material domain and the other of the first anode active material domain or the first conductive material domain.

[0047] The soft block may include repeating units derived from an aliphatic diene monomer and / or an alicyclic diene monomer and exhibit a rubber phase at room temperature, specifically, may be derived from an aliphatic diene monomer including at least one selected from butadiene monomers, pentadiene monomers, and hexadiene monomers.

[0048] The butadiene-based monomer may include at least one selected from the group consisting of 1,2-butadiene, 1,3-butadiene, isoprene, and chloroprene.

[0049] The pentadiene-based monomer may include at least one selected from the group consisting of 1,2-pentadiene, 1,3-pentadiene, 1,4-pentadiene, 2,3-pentadiene, 2-methyl-1,3-pentadiene, 2-methyl-1,4-pentadiene, 2-methyl-2,3-pentadiene, 2-methyl-2,4-pentadiene, 3-methyl-1,3-pentadiene, 3-methyl-1,4-pentadiene, 4-methyl-1,3-pentadiene, 2-ethyl ... pentadiene, 2-ethyl-1,4-pentadiene, 2-ethyl-2,4-pentadiene, 3-ethyl-1,3-pentadiene, 3-ethyl-1,4-pentadiene, 4-ethyl-1,3-pentadiene, 1-chloro-1,3-pentadiene, 1-chloro-2,4-pentadiene, 2-chloro-1,3-pentadiene, 3-chloro-1,3-pentadiene, 3-chloro-1,4-pentadiene, and 5-chloro-1,3-pentadiene.

[0050] The hexadiene-based monomer may include at least one selected from the group consisting of 1,2-hexadiene, 1,3-hexadiene, 1,4-hexadiene, 1,5-hexadiene, 2,3-hexadiene, 2,4-hexadiene, 2,5-hexadiene, 3,5-hexadiene, 2-methyl-1,3-hexadiene, 2-methyl-1,4-hexadiene, 2-methyl-1,5-hexadiene, 2-methyl-2,3-hexadiene, 2-methyl-2,4-hexadiene, 3-methyl-1,2-hexadiene, 3-methyl-1,3-hexadiene, 3-methyl-1,4-hexadiene. ethyl-1,3-hexadiene, 2-ethyl-1,4-hexadiene, 3-ethyl-1,2-hexadiene, 3-ethyl-1,3-hexadiene, 3-ethyl-1,4-hexadiene and 3-ethyl-1,5-hexadiene.

[0051] The soft block can be used to provide flexibility to the triblock copolymer and improve extrusion properties and abrasion resistance.

[0052] The first hard block and the second hard block may include repeating units derived from an ethylenically unsaturated monomer containing an aromatic ring and exhibit a glass phase at room temperature. Specifically, the aromatic ring contained in the ethylenically unsaturated monomer may be a substituted or unsubstituted benzene ring or a substituted or unsubstituted naphthalene ring.

[0053] In addition, the aromatic ring may be connected to the main chain or the side chain of the repeating unit of the first hard block and the second hard block, and may be preferably connected to the side chain of the repeating unit of the first hard block and the second hard block.

[0054] The first hard block and the second hard block may each independently be derived from an aromatic ring-containing ethylenically unsaturated monomer including at least one of a styrene-based monomer and an aromatic (meth)acryloyl-based monomer.

[0055] The styrene-based monomer may include at least one selected from the group consisting of styrene, α-methylstyrene, p-methylstyrene, p-methoxystyrene, p-ethoxystyrene, tert-butoxystyrene, p-acetoxystyrene, p-chlorostyrene, p-bromostyrene, 2,4-dimethylstyrene, 3,5-dimethylstyrene, and 2,4,6-trimethylstyrene.

[0056] The aromatic (meth)acryloyl monomer may include at least one selected from the group consisting of benzyl acrylate, benzyl methacrylate, phenoxy acrylate, phenoxy methacrylate, phenyl acrylate, phenyl methacrylate, phenethyl acrylate, and phenethyl methacrylate.

[0057] The first hard block and the second hard block can be firmly bonded to the first anode active material or the first conductive material through π-π interactions generated by the aromatic ring structure contained in the repeating unit. Additionally, the first hard block and the second hard block can provide high strength properties to the triblock copolymer including the first hard block and the second hard block.

[0058] In an embodiment, the amount of the first hard block and the second hard block can be 10 wt% to 60 wt%, preferably 15 wt% to 55 wt%, more preferably 20 wt% to 50 wt% based on the total amount of the triblock copolymer. When the amount of the first hard block and the second hard block satisfies the above numerical range, the binding strength can be further improved due to the strong interaction with the first negative active material or the first conductive material, and the triblock copolymer can have appropriate flexibility to have much better molding properties.

[0059] In an embodiment, the weight-average molecular weight of each of the first hard block and the second hard block can be 9,000 g / mol to 20,000 g / mol, preferably 9,500 g / mol to 20,000 g / mol, more preferably 10,000 g / mol to 20,000 g / mol. When the weight-average molecular weight of each of the first hard block and the second hard block satisfies the above numerical range, the physical crosslinking force between the first binder and the first anode active material or the first conductive material can be improved to form a more stable three-dimensional network structure, and it can be easily deformed during the manufacture of the electrode to further improve the processability.

[0060] The first anode active material can include at least one selected from carbon-based active materials, silicon-based active materials, metal-based active materials that can be alloyed with lithium, and lithium-containing active materials.

[0061] The carbon-based active material can be, for example, graphite, hard carbon, soft carbon, or graphene. The graphite can be artificial graphite, natural graphite, a mixture of artificial graphite and natural graphite, natural graphite coated with artificial graphite, or a combination thereof.

[0062] The change in the crystal structure of the carbon-based active material during the insertion and extraction of lithium ions is very small, so it can allow continuous and repeated redox reactions at the electrode to obtain a lithium secondary battery with high capacity and longer life.

[0063] The silicon-based active material can be, for example, Si, SiO m , Si-C composite material, Si-Q alloy, or a combination thereof, where m satisfies 0 < m ≤ 2, Q can be an alkali metal, alkaline earth metal, group 13 to group 16 element, transition metal, rare earth element, or a combination thereof, and Q does not include Si.

[0064] The metal-based active material that can be alloyed with lithium can be, for example, B, Al, Ga, In, Ge, Sn, Pb, P, As, Sb, Bi, Mg, Ca, Zn, Cd, Pd, Ag, Au, Pt, their alloys, or their oxides.

[0065] The lithium-containing active material may be, for example, a lithium-containing titanium composite oxide (LTO).

[0066] The first conductive material may include at least one selected from graphite, activated carbon, carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene, and carbon fibers.

[0067] In an embodiment, any one of the first anode active material domain or the first conductive material domain and the other of the first anode active material domain or the first conductive material domain can be connected to form a three-dimensional network structure by a first binder in the form of a discontinuous column (or line). That is, any surface of the first anode active material domain or the first conductive material domain and the other surface of the first anode active material domain or the first conductive material domain can be connected by a binder in the form of a discontinuous column (or line) to form a composite with a three-dimensional network structure in the form of a mesh (active material or conductive material is located at the intersection, and a linear binder connects these materials).

[0068] This three-dimensional network structure can be generated by the strong π-π interaction between the first hard block and the second hard block contained in the triblock copolymer and the first anode active material or the first conductive material. In this case, the first anode active material domain or the first conductive material domain and the first binder in the form of a discontinuous column can be connected to form a three-dimensional network structure, whereby the first self-supporting film can have excellent tensile strength.

[0069] In an embodiment, the first binder may have an average width perpendicular to the longitudinal direction of 0.1 μm to 2 μm, preferably 0.2 μm to 0.8 μm, and more preferably 0.3 μm to 0.7 μm. In this case, for the first binder in the form of a column contained in the first self-supporting film, the average width perpendicular to the longitudinal direction refers to: an image of the first binder particles observed using a scanning electron microscope (SEM), by measuring the width perpendicular to the longitudinal direction at both ends and the center of five randomly selected columnar first binders along the longitudinal direction, and taking the average value of these measured values.

[0070] In an embodiment, the first glass transition temperature and the second glass transition temperature corresponding to the first hard block and the second hard block, respectively, may be 50°C to 120°C, and the third glass transition temperature corresponding to the soft block may be -120°C to -50°C. Preferably, the first glass transition temperature and the second glass transition temperature may be 80°C to 120°C, and the third glass transition temperature may be -120°C to -80°C, more preferably, the first glass transition temperature and the second glass transition temperature may be 80°C to 110°C, and the third glass transition temperature may be -110°C to -80°C. Therefore, the first hard block, the second hard block, and the soft block contained in the triblock copolymer have a glass transition temperature within the above numerical range, and accordingly, the first self-supporting film containing the first binder containing the triblock copolymer may have further improved durability and flexibility, and may further more effectively maintain the shape.

[0071] The soft block, the first hard block and the second hard block contained in the triblock copolymer can exhibit independent properties without affecting each other, so the soft block can provide appropriate flexibility, and the first hard block and the second hard block can each provide a strong bonding strength with the first anode active material or the first binder to the first self-supporting film.

[0072] Second self-supporting film

[0073] The second self-standing film includes a second binder, a second anode active material, and a second conductive material.

[0074] The second binder may include a fluorine-based resin. The fluorine-based resin may be in the form of fibers and may serve as a matrix that supports and combines the second anode active material and the second conductive material.

[0075] The fluorine-based resin may include, for example, at least one selected from the group consisting of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyvinylidene fluoride-trifluoroethylene (PVDF-TrFE), polyvinylidene fluoride-tetrafluoroethylene (PVDF-TFE), polyvinylidene fluoride-chlorofluoroethylene (PVDF-CTFE), and polytetrafluoroethylene (PTFE).

[0076] The second anode active material may include at least one selected from a carbon-based active material, a silicon-based active material, a metal-based active material alloyable with lithium, and a lithium-containing active material. In this case, the second anode active material may be the same as or different from the first anode active material.

[0077] The carbon-based active material may be, for example, graphite, hard carbon, soft carbon, or graphene. The graphite may be artificial graphite, natural graphite, a mixture of artificial graphite and natural graphite, natural graphite coated with artificial graphite, or a combination thereof.

[0078] During the insertion and extraction of lithium ions, the carbon-based active material undergoes little change in crystal structure, thus allowing continuous and repeated redox reactions at the electrode to obtain a lithium secondary battery with high capacity and longer lifespan.

[0079] The silicon-based active material can be, for example, Si, SiO m , Si-C composite, Si-Q alloy, or a combination thereof, where m satisfies 0 < m ≤ 2, Q can be an alkali metal, alkaline earth metal, Group 13 to 16 element, transition metal, rare earth element, or a combination thereof, and Q does not include Si.

[0080] The metal-based active material that can alloy with lithium can be, for example, B, Al, Ga, In, Ge, Sn, Pb, P, As, Sb, Bi, Mg, Ca, Zn, Cd, Pd, Ag, Au, Pt, their alloys, or their oxides.

[0081] The lithium-containing active material can be, for example, lithium-containing titanium composite oxide (LTO).

[0082] The second conductive material can include at least one selected from graphite, activated carbon, carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene, and carbon fiber. In this case, the second conductive material can be the same as or different from the first conductive material.

[0083] Laminate

[0084] The laminate can include a first self-supporting film and a second self-supporting film.

[0085] The first self-supporting film can include a first binder containing a triblock copolymer and has excellent mechanical properties derived from the first hard block and the second hard block of the triblock copolymer, as well as excellent adhesion to the current collector due to the π-π interaction generated by the aromatic ring structure contained in the repeating units of the first hard block and the second hard block.

[0086] The second self-supporting film can include a second binder containing a fluorine-based resin. Specifically, the second binder containing fibrous fluorine-based resin can have excellent flexibility derived from the fibrous binder.

[0087] As described above, the first self-supporting film and the second self-supporting film include different types of binders. Therefore, the first self-supporting film and the second self-supporting film can have different physical properties. That is, the first self-supporting film can have better mechanical properties and greater adhesion to the current collector than the second self-supporting film, and the second self-supporting film can have greater flexibility than the first self-supporting film.

[0088] In this case, the laminate including both the first self-standing film and the second self-standing film can well balance the combination of excellent mechanical properties derived from the first self-standing film, excellent adhesion to the current collector, and excellent flexibility derived from the second self-standing film.

[0089] In an embodiment, the laminate may have an average thickness of 30 μm to 500 μm, preferably 100 μm to 400 μm, more preferably 150 μm to 250 μm. In this case, when the average thickness of the laminate satisfies the above range, the laminate can obtain sufficient mechanical properties and also obtain low resistance to have improved output characteristics when applied to lithium secondary batteries.

[0090] In an embodiment, the laminate may have various types of stacking structures including the first self-supporting film and the second self-supporting film. For example, the laminate may have a double-layer structure in which the first self-supporting film and the second self-supporting film are sequentially stacked. For another example, the laminate may have a three-layer structure in which the first self-supporting film is stacked on each side of the upper side and the lower side of the second self-supporting film. For another example, the laminate may have a structure including a repeated alternating stacking structure of the first self-supporting film and the second self-supporting film (for example, a four-layer structure of the first self-supporting film / the second self-supporting film / the first self-supporting film / the second self-supporting film or a stacking structure having more than four layers of overlap). Therefore, when the laminate has a structure including a repeated three-layer structure or an alternating stacking structure, the laminate may have further improved physical properties due to the self-supporting films with different physical properties being evenly distributed throughout the laminate.

[0091] In an embodiment, the thickness ratio of the first self-supporting film to the second self-supporting film may be 1: 0.01 to 1: 0.49, 1: 0.05 to 0.42, 1: 0.07 to 0.35, or 1: 0.1 to 0.29. In this case, when the thickness ratio of the first self-supporting film to the second self-supporting film satisfies the above range, the laminate can fully ensure the excellent physical properties derived from the first self-supporting film and the second self-supporting film, and the content of the triblock copolymer having excellent stability at a negative potential can be much greater than the content of the fluorine-based resin having relatively low stability compared to the triblock copolymer at a negative potential, so as to further improve the life characteristics of the lithium secondary battery to which the laminate is applied.

[0092] Anode for lithium secondary battery

[0093] The anode for a lithium secondary battery of the present invention comprises the above-mentioned self-supporting film for an anode for a lithium secondary battery and a current collector.

[0094] The collector is not particularly limited as long as the collector has high conductivity and does not cause chemical changes in the anode. For example, stainless steel, aluminum, nickel, titanium, sintered carbon, copper, their alloys, or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used as the collector.

[0095] In the self-supporting film laminate for lithium secondary battery anode, the collector can be arranged on one side of the first self-supporting film as the outermost layer. As described above, the triblock copolymer contained in the first self-supporting film can have excellent adhesion to the collector through the π-π interaction generated by the aromatic ring structure contained in the repeating unit of the first hard block and the second hard block, so when the collector is arranged on one side of the first self-supporting film, the adhesion between the self-supporting film laminate for lithium secondary battery anode and the collector can be improved.

[0096] In an embodiment, in the current collector, a primer layer comprising a carbon-based material may be formed on a surface of one side of a self-supporting film laminate for a lithium secondary battery anode. The carbon-based material may include, for example, at least one selected from graphite, graphene, carbon black, superconductive carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon nanotubes, graphite fibers, and carbon fibers.

[0097] The carbon-based material contained in the primer layer can have excellent adhesion to the first self-supporting film through the π-π interaction with the aromatic ring structure contained in the repeating unit of the first hard block and the second hard block. Therefore, when the primer layer is formed, the adhesion between the self-supporting film laminate for the anode of the lithium secondary battery and the collector can be further improved.

[0098] Lithium secondary battery

[0099] The lithium secondary battery of the present invention may include the above-mentioned anode for a lithium secondary battery, cathode for a lithium secondary battery, and an electrolyte.

[0100] The cathode for a lithium secondary battery may include at least one cathode active material selected from lithium, nickel, cobalt, manganese, iron, tin, silicon, aluminum, and mixtures thereof. For example, for a cathode for a lithium secondary battery, a material such as LiCoO 2 、LiMnO 2 、LiFeO 2 、Li(Ni 0.6 Mn 0.2 Co 0.2 ) 2 、Li(Ni 0.7 Mn 0.15 Co 0.15 ) 2 、Li(Ni 0.8 Mn 0.1 Co 0.1 ) 2 、Li(Ni 0.9 Mn 0.05 Co 0.05 ) 2、LiNi 0.6 Co 0.2 0A 0.2 O 2 、LiNi 0.7 Co 0.2 0A 0.1 O 2 、LiNi 0.8 Co 0.15 Al 0.05 O 2 、LiNi 0.85 Co 0.1 Al 0.05 O 2 、LiNi 0.88 Co 0.1 Al 0.02 O 2 、LiMn 2 O 4 and LiFePO 4 cathode active material.

[0101] The electrolyte may be a liquid electrolyte or a solid electrolyte.

[0102] When the electrolyte is a liquid electrolyte, the electrolyte may contain a lithium salt and a non-aqueous organic solvent.

[0103] As long as the lithium salt is commonly used in the electrolyte of lithium secondary batteries, the lithium salt can be applied without limitation. For example, the lithium salt may include a lithium ion battery selected from LiPF 6 , LiBF 4 、LiSbF 6 、LiAsF 6 、LiN(C 2 F 5 SO 2 ) 2 、LiN(CF 3 SO 2 ) 2 CF 3 SO 3 Li、LiC(CF 3 SO 2 ) 3 ,LiC 4 BO 8 , LiTFSI, LiFSI and LiClO 4 at least one compound in .

[0104] The non-aqueous organic solvent may include a type of organic solvent that can be used as a non-aqueous electrolyte when manufacturing a typical lithium secondary battery. In this case, the content of the non-aqueous organic solvent may be appropriately adjusted within a generally acceptable range.

[0105] Specifically, the nonaqueous organic solvent may include typical organic solvents usable as nonaqueous organic solvents for lithium secondary batteries, such as cyclic carbonate solvents, linear carbonate solvents, ester solvents, or ketone solvents, and these solvents may be used alone or in combination of two or more.

[0106] The cyclic carbonate solvent may include at least one selected from the group consisting of ethylene carbonate (EC), vinylene carbonate (VC), fluoroethylene carbonate (FEC), propylene carbonate (PC), and butylene carbonate (BC).

[0107] The linear carbonate solvent may include at least one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), and ethyl propyl carbonate (EPC).

[0108] The ester solvent may include at least one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, δ-valerolactone, and ε-caprolactone.

[0109] As the ketone solvent, polymethyl vinyl ketone or the like can be used.

[0110] When the electrolyte is a liquid electrolyte, the lithium secondary battery may further include a separator.

[0111] As a separator, a commonly used porous polymer film, for example, a porous polymer film prepared from a polyolefin-based polymer (e.g., ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer) can be used alone or laminated therewith, or a typical porous non-woven fabric can be used, for example, a non-woven fabric formed of high melting point glass fiber or polyethylene terephthalate fiber, but the separator is not limited thereto. In addition, a coated separator including a ceramic component or a polymer component can be used to ensure heat resistance or mechanical strength, and a separator having a single-layer or multi-layer structure can be used.

[0112] In this case, the porous separator may generally have a pore size of 0.01 μm to 50 μm, and a porosity of 5% to 95%. In addition, the porous separator may generally have a thickness of 5 μm to 300 μm.

[0113] Meanwhile, when the electrolyte is a solid electrolyte, the electrolyte may be a polymer-based solid electrolyte, an oxide-based solid electrolyte, a sulfide-based solid electrolyte, or a mixture thereof.

[0114] The polymer solid electrolyte may include, for example, polyether-based polymers, polycarbonate-based polymers, acrylate-based polymers, polysiloxane-based polymers, phosphazene-based polymers, polyethylene derivatives, alkylene oxide derivatives (e.g., polyethylene oxide), phosphate polymers, poly-stirred lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride and derivatives thereof, polymers containing ion dissociation groups. In addition, the polymer electrolyte is a polymer resin, and may be, for example, a branched copolymer, in which an amorphous polymer such as PMMA, polycarbonate, polysiloxane and / or phosphazene is copolymerized with a PEO (polyethylene oxide) main chain as a comonomer, may include a comb-like polymer resin and a cross-linked polymer resin, and at least one of them.

[0115] The oxide-based solid electrolyte may be, for example, a LLZO-based compound, a LLTO-based compound, such as Li 3x La 2 / 3- x TiO 3 , LISICON-based compounds, such as Li 14 Zn(GeO 4 ) 4 , LATP-based compounds, such as Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 , LAGP-based compounds, such as (Li 1+x Ge 2-x Al x (PO 4 ) 3 ), and LIPON-based compounds, but are not particularly limited thereto.

[0116] The sulfide-based solid electrolyte may include at least one of the following: Li 6 PS 5 Cl, Li 2 SP 2 S 5 , Li 2 S-LiI-P 2 S 5 , Li 2 S-LiI-Li 2 OP 2 S 5 , Li 2 S-LiBr-P 2 S 5 , Li 2 S-Li 2 OP 2 S 5 , Li 2 SLi3 PO 4 -P 2 S 5 , Li 2 SP 2 S 5 -P 2 O 5 , Li 2 SP 2 S 5 -SiS 2 , Li 2 SP 2 S 5 -SnS、Li 2 SP 2 S 5 -Al 2 S 3 , Li 2 S-GeS 2 or Li 2 S-GeS 2 -ZnS, but not particularly limited thereto.

[0117] Method for producing a self-supporting film laminate for lithium secondary battery anode

[0118] Hereinafter, a method for manufacturing a self-standing film laminate for a lithium secondary battery anode of the present invention will be described, and the self-standing film laminate for a lithium secondary battery anode and components included therein will not be repeatedly described.

[0119] A method of manufacturing a self-standing film laminate for a lithium secondary battery anode may include stacking a first self-standing film and a second self-standing film.

[0120] In an embodiment, stacking may include calendaring (rolling). That is, the first self-supporting film and the second self-supporting film may be overlapped, passed between a pair of rollers, and pressed and rolled to form a self-supporting film laminate for a lithium secondary battery anode.

[0121] In this case, when the self-supporting film laminate for the anode of a lithium secondary battery includes two or more first self-supporting films and / or two or more second self-supporting films (for example, a three-layer structure of a first self-supporting film / a second self-supporting film / a first self-supporting film), the stacking may include overlapping and arranging a plurality of self-supporting films constituting the self-supporting film laminate for the anode of a lithium secondary battery in a stacking order, and then passing the self-supporting film between a pair of rollers for pressing and rolling. That is, the stacking of the first self-supporting film and the second self-supporting film may be to alternately stack the first self-supporting film and the second self-supporting film.

[0122] In an embodiment, the stacking of the first self-supporting film and the second self-supporting film can be performed at 50°C to 160°C, 60°C to 130°C, or 80°C to 120°C, preferably at a temperature equal to or higher than the first glass transition temperature and the second glass transition temperature corresponding to the first hard block and the second hard block, respectively, and equal to or higher than the glass transition temperature of the fluorine-based resin. In this case, when the stacking of the first self-supporting film and the second self-supporting film is performed within the above temperature range, the fluidity and formability of the first adhesive and the second adhesive during stacking can be fully ensured, and accordingly, the adhesion between the first self-supporting film and the second self-supporting film can be further improved.

[0123] In an embodiment, the method for manufacturing a self-supporting film laminate for a lithium secondary battery anode may include a film-making process for independently manufacturing a first self-supporting film and a second self-supporting film. That is, the method for manufacturing a self-supporting film laminate for a lithium secondary battery anode may include stacking a first self-supporting film and a second self-supporting film respectively manufactured by different film-making processes.

[0124] In an embodiment, the first self-supporting film can be obtained by a film-making process using a composition for forming a first self-supporting film comprising a first anode active material, a first conductive material and a first binder. In this case, the first binder in the composition for forming the first self-supporting film may include an average diameter (D 50 ) is 1 μm to 50 μm of triblock copolymer particles. The average diameter (D 50 ) represents a diameter corresponding to 50% of the volume cumulative distribution measured using a laser diffraction / scattering particle size distribution measuring instrument.

[0125] The first binder in the composition for forming the first self-supporting film is substantially spherical, and may be a true sphere or an almost true sphere, and specifically may have an average sphericity of 0.7 to 1.0, preferably 0.8 to 1.0, and more preferably 0.9 to 1.0. That is, before manufacturing the first self-supporting film, the particles of the first binder in the composition for forming the first self-supporting film containing the first binder may be dispersed in the composition for forming the first self-supporting film while substantially maintaining a spherical shape.

[0126] In this case, the sphericity of the first binder in the composition for forming the first self-standing film is a value obtained by observing an image of binder particles using a scanning electron microscope (SEM), measuring the major and minor axes of 10 randomly selected particles, calculating the minor axis / major axis ratio of each particle, and determining the average value of the minor axis / major axis ratio, and the closer the sphericity is to 1, the more spherical the particle is.

[0127] In an embodiment, the film-making process of the first self-supporting film can be carried out by calendaring (rolling). That is, the composition for forming the first self-supporting film containing the first anode active material, the first conductive material and the first binder can be passed between a pair of rollers, subjected to pressing and rolling to form the first self-supporting film.

[0128] In this case, at the beginning of the membrane forming process, the first binder containing a substantially spherical triblock copolymer is in contact with the first anode active material or the first conductive material through a high external force (shear force, tension, etc.), and then as the external force decreases at the rear end of the membrane forming process, the distance between the first anode active material or the first conductive material increases, so that the first binder containing the triblock copolymer in contact with the surface of the first anode active material or the first conductive material can be flexibly deformed while maintaining adhesion, thereby forming a non-continuous columnar or linear form.

[0129] In an embodiment, the film-making of the first self-supporting film can be carried out at a temperature equal to or higher than the first glass transition temperature and the second glass transition temperature corresponding to the first hard block and the second hard block, respectively. The first hard block and the second hard block are cross-linked (connected) by a physical bond with a relatively low bonding energy, and therefore can maintain the same form and size below the glass transition temperature, but can be easily formed when it is higher than the glass transition temperature. Therefore, when the film-making process of the first self-supporting film is carried out at a temperature equal to or higher than the first glass transition temperature and the second glass transition temperature, each hard block contained in the triblock copolymer is flexibly deformed while maintaining bonding with the first anode active material or the first conductive material, so the first binder part can provide a physical cross-linking point (connection point) in the form of a linear (non-continuous columnar or linear) to form a solid three-dimensional network structure around the point.

[0130] In an embodiment, the second self-standing film may be obtained by a film-making process using a composition for forming a second self-standing film including a second anode active material, a second conductive material, and a second binder.

[0131] In an embodiment, the film-making process of the second self-supporting film can be carried out by calendaring (rolling). That is, the composition for forming the second self-supporting film containing the second anode active material, the second conductive material and the second binder can be passed between a pair of rollers, subjected to pressing and rolling to form the second self-supporting film.

[0132] In an embodiment, the film formation of the second self-supporting film can be carried out at 60° C. to 160° C., 70° C. to 150° C., or 75° C. to 145° C., preferably at a temperature equal to or higher than the glass transition temperature of the fluorine-based resin. In this case, when the film formation of the self-supporting film is carried out at the above temperature, sufficient flexibility of the second binder can be obtained, so that the bonding between the second binder and the second anode active material and / or the second conductive material is effectively maintained, and the second binder can be flexibly deformed to facilitate the molding of the second self-supporting film.

[0133] In the embodiment, the film-making process of the first self-supporting film and the film-making process of the second self-supporting film can both be carried out using a dry method. That is, the first self-supporting film and the second self-supporting film are both manufactured by a dry method, and the composition for forming the first self-supporting film and the composition for forming the second self-supporting film can be substantially free of solvent. When the film-making process is carried out using a wet method, the load of the electrode is limited due to the liquid slurry, and in some cases, the network structure between the binder and the active material / conductive material may not be formed, but, since the film-making process according to the present invention is carried out using a dry method, a high electrode load allowing a high energy density can be obtained, and a network structure can be more effectively formed between the binder and the active material.

[0134] Method for manufacturing anode for lithium secondary battery

[0135] Hereinafter, a method for manufacturing an anode for a lithium secondary battery according to the present invention will be described, and the anode for a lithium secondary battery and components included therein will not be repeatedly described.

[0136] The method for manufacturing an anode for a lithium secondary battery may include the method for manufacturing a self-standing film laminate for a lithium secondary battery anode as described above, and disposing a current collector on one side of the first self-standing film as the outermost layer in the self-standing film laminate for anode for a lithium secondary battery.

[0137] In the embodiment, the current collector can be arranged by calendering (rolling). That is, when the first self-supporting film as the outermost layer in the self-supporting film laminate for the anode of a lithium secondary battery and the current collector are arranged relative to each other, the current collector and the self-supporting film laminate for the anode of a lithium secondary battery can be passed between a pair of rollers, and subjected to pressing and rolling to form an anode for a lithium secondary battery.

[0138] In an embodiment, the arrangement (e.g., calendering) of the current collector may be performed at 80°C to 200°C, 90°C to 170°C, or 95°C to 145°C, preferably at a temperature equal to or higher than the first glass transition temperature and the second glass transition temperature corresponding to the first hard block and the second hard block, respectively. In this case, when the arrangement of the current collector is performed within the above temperature range, sufficient adhesion can be obtained between the current collector and the first self-supporting film.

[0139] Hereinafter, the present invention will be described in more detail by way of examples. However, these embodiments are provided to help understand the present invention, and the scope of the present invention is not limited to these embodiments in any sense.

[0140] Example 1 A self-supporting film laminate for a lithium secondary battery anode, wherein the first self-supporting film and the second self-supporting film are stacked Overlap

[0141] Manufacturing Example 1-1: Manufacturing of a first self-supporting film containing an SBS binder

[0142] Graphite as an anode active material, carbon black as a conductive material, and SBS triblock copolymer (glass transition temperature of polystyrene block: 100° C., glass transition temperature of polybutadiene block: −100° C.) as a binder were mixed at a mass ratio of 96:1:3 without a solvent.

[0143] The mixed powder was rolled into a free-standing film using a twin roll press heated to 120°C.

[0144] Manufacturing Example 1-2: Manufacturing of a Second Self-Supporting Film Containing a PTFE Binder

[0145] Graphite as an anode active material, carbon black as a conductive material, and PTFE as a binder were mixed at a mass ratio of 96:1:3 without a solvent.

[0146] The mixed powder was rolled into a free-standing film using a twin roll press heated to 80°C.

[0147] Manufacturing Examples 1-3: Manufacturing of Laminated Boards

[0148] The first self-supporting film (Manufacturing Example 1-1) and the second self-supporting film (Manufacturing Example 1-2) were overlapped and then roll-pressed using a twin roll press heated to 100° C., thereby manufacturing a laminate.

[0149] In this case, the manufactured laminate had an average thickness of 200 μm, and the thickness ratio of the first self-supporting film to the second self-supporting film included in the laminate was 1:0.25.

[0150] Comparative Example 1: Self-supporting film for lithium secondary battery anode containing PTFE as a binder

[0151] Graphite as an anode active material, carbon black as a conductive material, and PTFE as a binder were mixed at a mass ratio of 96:1:3 without a solvent.

[0152] The mixed powder was roll-pressed using a twin roll press heated to 80° C. to produce a self-standing film having an average thickness of 200 μm.

[0153] Reference Example 1: Self-supporting film for lithium secondary battery anode containing SBS as a binder

[0154] Graphite as an anode active material, carbon black as a conductive material, and SBS triblock copolymer (glass transition temperature of polystyrene block: 100° C., glass transition temperature of polybutadiene block: −100° C.) as a binder were mixed at a mass ratio of 96:1:3 without a solvent.

[0155] The mixed powder was roll-pressed using a twin roll press heated to 120° C. to produce a self-standing film having an average thickness of 200 μm.

[0156] Experimental Example 1: SEM images of the mixed powder in Manufacturing Example 1-1 and the first self-standing film manufactured therefrom observe

[0157] The SEM image of the first self-supporting film manufactured according to Manufacturing Example 1-1 was taken, as shown in FIG. Figure 1A and Figure 1B As shown, before manufacturing the first self-supporting film, a SEM image of a mixed powder of an anode active material (graphite), a conductive material (carbon black), and a first binder (SBS triblock copolymer) is taken, as shown in FIG. Figure 2A In this case, only the SBS powder was taken. Figure 2B middle.

[0158] Reference Figure 1A and Figure 1B It can be seen that after the film making process, the columnar SBS binder forms a network structure connection between the anode active materials, between the conductive materials, or between the anode active materials and the conductive materials, and is in a columnar form with an average width perpendicular to the longitudinal direction of about 0.4 μm to 0.5 μm.

[0159] Figure 1C The columnar SBS binder connecting either the anode active material or the conductive material with the other of the anode active material or the conductive material in the network structure of the first self-supporting film manufactured according to Manufacturing Example 1-1 is schematically shown. In this case, it can be seen that the SBS binder in the form of a discontinuous column makes point contact with the outer surface of each of the active material domains or the conductive material domains, thereby generating a structure connecting these domains.

[0160] Reference Figure 2A, it can be seen that the SBS is dispersed in the mixed powder while maintaining an almost spherical shape (average diameter (D 50 ): 8 μm, average sphericity: 0.95), such as Figure 2B As shown, before making the above mixed powder, the SBS powder is also almost spherical.

[0161] Experimental Example 2: Evaluation of the adhesion of the current collector

[0162] Anodes for lithium secondary batteries were manufactured by rolling a current collector (copper foil with a thickness of 8 μm obtained from Nexilis) coated with a primer layer (Ketjen Black) and the self-supporting film laminate of Example 1, the self-supporting film of Comparative Example 1, and the self-supporting film of Reference Example 1 using a double roll press heated to 100° C. In this case, the first self-supporting film included in the self-supporting film laminate of Example 1 was arranged to face the primer layer coated on the current collector.

[0163] Thereafter, the current collector and the self-supporting film laminate or the self-supporting film were subjected to a peeling test according to the standard of ASTM D1876, and the results are shown in Table 1 below.

[0164] Experimental Example 3: Evaluation of Flexibility

[0165] A cylindrical bar having an average diameter of 10 mm was wrapped with the self-standing film laminate of Example 1, the self-standing film of Comparative Example 1, and the self-standing film of Reference Example 1, and the occurrence of cracks was visually evaluated. The results are shown in Table 1 below.

[0166] Experimental Example 4: Evaluation of tensile strength and elongation

[0167] In order to evaluate the tensile strength of the self-supporting film laminate of Example 1, the self-supporting film of Comparative Example 1, and the self-supporting film of Reference Example 1, each self-supporting film was punched out to have a width of 2 cm and a height of 6 cm to prepare a sample, and the sample was stretched at a rate of 5 mm / min using a UTM device while being measured to obtain a strain-length dependence graph of stress, and the tensile strength and elongation were measured based on the graph, and the results are shown in Table 1 below.

[0168] In this case, the tensile strength is measured by dividing the tensile stress measured in the graph by the cross-sectional area of ​​the sample, and the elongation is measured as the ratio of the strain length between the yield stress and the tensile stress measured in the graph.

[0169] [Table 1]

[0170]

[0171] Referring to Table 1, it was confirmed that the self-standing film laminate of Example 1 had excellent adhesion to the current collector and excellent tensile strength.

[0172] In addition, it was confirmed that the self-standing film laminate of Example 1 had a relatively low elongation at a level suitable for application to a roll-to-roll process, and also had excellent flexibility (see Figure 3A ).

[0173] On the contrary, it was determined that the self-supporting film of Comparative Example 1 had excellent flexibility (reference Figure 3B ), but had poor adhesion to the collector and poor tensile strength compared to the self-supporting film laminate of Example 1, and it was determined that the self-supporting film of Reference Example 1 had poor flexibility compared to the self-supporting film laminate of Example 1 (reference Figure 3C ) and excessive elongation.

[0174] Experimental Example 5: Evaluation of tensile strength according to the width of the produced film

[0175] The tensile strengths of the self-standing film laminate of Example 1, the self-standing film of Comparative Example 1 and the self-standing film of Reference Example 1 were measured when the width of the produced film was set to 100 mm, 200 mm and 300 mm, and the results are shown in Table 2 below.

[0176] In this case, the tensile stress measured in Experimental Example 4 was multiplied by the cross-sectional area of ​​each of the self-standing film laminates or self-standing films having different produced film widths to measure the tensile strength.

[0177] [Table 2]

[0178]

[0179] Referring to Table 2, like the self-standing film of Reference Example 1, the self-standing film laminate of Example 1 exhibited excellent total tensile strength regardless of the film manufacturing width value of 100 mm, 200 mm, or 300 mm.

[0180] In contrast, the self-standing film of Comparative Example 1 showed poor tensile strength at all film manufacturing widths of 100 mm, 200 mm, and 300 mm, and it was less than the minimum tensile strength of 5N used in a commonly used rolling apparatus.

[0181] The self-supporting film laminate for lithium secondary battery anode of the present invention can have excellent adhesion (derived from the triblock copolymer contained in the first self-supporting film as a binder), excellent mechanical properties and satisfactory elongation, and excellent flexibility (derived from the fluorine-based resin contained in the second self-supporting film as a binder).

[0182] While the present invention has been shown and described in connection with the exemplary embodiments, it will be apparent to those skilled in the art that modifications and variations can be made without departing from the spirit and scope of the invention as defined by the appended claims.

Claims

1. A self-supporting film laminate suitable for a lithium secondary battery anode, the self-supporting film laminate comprising: a first self-standing film comprising a first anode active material, a first conductive material, and a first binder comprising a triblock copolymer; and a second self-standing film comprising a second anode active material, a second conductive material, and a second binder comprising a fluorine-based resin, The triblock copolymer comprises a soft block and a first hard block and a second hard block, wherein the soft block is derived from an aliphatic or alicyclic diene monomer and exhibits a rubber phase at room temperature, and the first hard block and the second hard block are each connected to two ends of the soft block, derived from an aromatic ring-containing ethylenically unsaturated monomer and exhibit a glass phase at room temperature, and The first binder is in the form of discontinuous columns connected between any one of i) the first anode active material domain or ii) the first conductive material domain and the other of a) the first anode active material domain or b) the first conductive material domain.

2. The self-supporting film laminate suitable for lithium secondary battery anode according to claim 1, wherein: A thickness ratio of the first self-supporting film to the second self-supporting film is 1:0.01 to 1:0.

49.

3. The self-supporting film laminate suitable for lithium secondary battery anode according to claim 1, comprising a three-layer structure, wherein: The first self-standing film is stacked on each of an upper side and a lower side of the second self-standing film. 4 . The self-supporting film laminate suitable for a lithium secondary battery anode according to claim 1 , comprising a structure of repeatedly alternating stacks of the first self-supporting film and the second self-supporting film.

5. The self-supporting film laminate suitable for lithium secondary battery anode according to claim 1, wherein: The first anode active material domains or the first conductive material domains are connected with a first binder in the form of discontinuous columns to form a three-dimensional network structure.

6. The self-supporting film laminate suitable for lithium secondary battery anode according to claim 1, wherein: The first binder has an average width perpendicular to a longitudinal direction of 0.1 μm to 2 μm.

7. The self-supporting film laminate suitable for lithium secondary battery anode according to claim 1, wherein: A first glass transition temperature and a second glass transition temperature corresponding to the first hard block and the second hard block, respectively, are independently 50° C. to 120° C., and The third glass transition temperature corresponding to the soft block is -120°C to -50°C.

8. The self-supporting film laminate suitable for lithium secondary battery anode according to claim 1, wherein: The soft block is derived from an aliphatic diene-based monomer including at least one selected from a butadiene-based monomer, a pentadiene-based monomer, and a hexadiene-based monomer.

9. The self-supporting film laminate suitable for lithium secondary battery anode according to claim 1, wherein: The first hard block and the second hard block are each independently derived from an aromatic ring-containing ethylenically unsaturated monomer including at least one of a styrene-based monomer and an aromatic (meth)acryloyl-based monomer.

10. The self-supporting film laminate suitable for lithium secondary battery anode according to claim 1, wherein: The fluorine-based resin includes at least one selected from the group consisting of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trifluoroethylene, polyvinylidene fluoride-tetrafluoroethylene, polyvinylidene fluoride-chlorofluoroethylene, and polytetrafluoroethylene.

11. An anode for a lithium secondary battery, comprising: Current collector; and The self-supporting film laminate suitable for lithium secondary battery anode according to claim 1, The current collector is provided on one side of a first self-supporting film as an outermost layer in a self-supporting film laminate suitable for a lithium secondary battery anode.

12. The anode for a lithium secondary battery according to claim 11, wherein The current collector includes a primer layer containing a carbon-based material formed on a surface of a side where a self-standing film laminate for a lithium secondary battery anode is provided.

13. A lithium secondary battery comprising: The anode for a lithium secondary battery according to claim 11; Cathodes for lithium secondary batteries; and Electrolytes.

14. A method for producing a self-supporting film laminate for a lithium secondary battery anode, the method comprising: stacking a first self-supporting film and a second self-supporting film, the first self-supporting film comprising a first anode active material, a first conductive material, and a first binder comprising a triblock copolymer, and the second self-supporting film comprising a second anode active material, a second conductive material, and a second binder comprising a fluorine-based resin, The triblock copolymer comprises a soft block and a first hard block and a second hard block, wherein the soft block is derived from an aliphatic or alicyclic diene monomer and exhibits a rubber phase at room temperature, and the first hard block and the second hard block are each connected to two ends of the soft block, derived from an aromatic ring-containing ethylenically unsaturated monomer and exhibit a glass phase at room temperature, and The first binder is in the form of discontinuous columns connected between any one of the first anode active material domain or the first conductive material domain and the other of the first anode active material domain or the first conductive material domain.

15. The method for producing a self-supporting film laminate for a lithium secondary battery anode according to claim 14, wherein: The first self-supporting film is obtained by a film-making process using a composition for forming a first self-supporting film comprising a first anode active material, a first conductive material, and a first binder, and The first binder in the composition for forming the first self-supporting film comprises an average particle size D 50 The triblock copolymer particles are 1 μm to 50 μm.

16. The method for producing a self-supporting film laminate for a lithium secondary battery anode according to claim 15, wherein: The first binder in the composition for forming a first self-standing film is spherical and includes particles having an average sphericity of 0.8 to 1.

0.

17. The method for producing a self-supporting film laminate for a lithium secondary battery anode according to claim 14, wherein: The first self-supporting film and the second self-supporting film are obtained by using a dry film forming process.

18. The method for producing a self-supporting film laminate for a lithium secondary battery anode according to claim 17, wherein: The film formation of the first self-standing film is performed at a temperature equal to or higher than the first glass transition temperature and the second glass transition temperature corresponding to the first hard block and the second hard block, respectively.

19. The method for producing a self-supporting film laminate for a lithium secondary battery anode according to claim 14, wherein: The stacking of the first self-standing film and the second self-standing film includes alternately stacking the first self-standing film and the second self-standing film.

20. A method for manufacturing an anode for a lithium secondary battery, the method comprising: The method for manufacturing a self-supporting film laminate for a lithium secondary battery anode according to claim 14; as well as The current collector is disposed on one side of the first self-standing film as the outermost layer in the self-standing film laminate for a lithium secondary battery anode.

Citation Information

Patent Citations

  • Laser drilling process for integrated circuit package

    KR1020230106488A